MANAJEMEN PENGEMBANGAN SDM BERBASIS PEMBELAJARAN KONTEKSTUAL TERHADAP PENINGKATAN KOMPETENSI DAN KOMITMEN ORGANISASI - Paeno Paeno; Kamsidik Kamsidik (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
This study aims to analyze the effect of human resource (HR) development management based on contextual learning on the improvement of employee competencies and organizational commitment. The research employs a quantitative approach using a survey method, involving 150 respondents consisting of employees and managers in educational and business sector organizations. Data were collected through structured questionnaires and analyzed using multiple linear regression to examine the relationships between variables. The results indicate that the implementation of contextual learning in HR development significantly enhances employee competencies, which in turn contributes to the improvement of organizational commitment. These findings underscore the importance of HR development strategies that emphasize real-world learning experiences, task relevance, and practical application in daily work. The study provides practical implications for HR managers in designing effective development programs to improve human resource quality and strengthen organizational commitment.